822 Lessons Learnt During the COVID-19 Pandemic on Emergency Surgical Admissions in A District General Hospital. (4th May 2021) - Ahn, K; Khan, N; Desai, N; Abdu, M; Hiddema, L; Odogwu, S; Cheetham, M; Pande, R
Abstract: Introduction: Coronavirus disease (COVID-19) is an acute severe respiratory distress syndrome which resulted in an unprecedented impact on NHS service provision. We aimed to assess the impact of COVID-19 on general surgical services in a district general hospital. Method: Electronic health care record data was retrospectively collected from 6th of April to 6th of May for both 2019 and 2020. Results: Despite fewer referrals and admissions in 2020 (133 vs 177 admissions in 2019), there were more failed discharges (29 vs 17 in 2019) and higher associated costs. Higher numbers of biliary related pathologies and pancreatitis (50 in 2020 vs 25 in 2019), and fewer complaints of non-specific abdominal pain (10 in 2020 vs 22 in 2019) were observed. The use of outpatient investigations decreased by approximately 40% in 2020; however, utilisation of inpatient investigations was comparable. Conclusions: Better utilisation of outpatient investigations and virtual clinic services may surmount pressures from further peaks of COVID-19. The increase in biliary related cases and pancreatitis may be consequent upon lifestyle changes during lockdown. This merits further investigation and if appropriate, public health intervention. In the absence of an efficacious vaccine, further research would be essential to streamline general surgical services based on clinical risk stratification.